Influence of environmental factors on wetland avian species in Paya Indah and Putrajaya wetlands using habitat suitability modelling - Chukwuemeka, Onwuka Martins (2020)
In Malaysia, multiple lands use has opened the way to substantial loss of wetland ecosystem, and shrinkage of the populations, habitat and food bases of avian species. However, the study of the avian populations and environmental factors affecting their diversity become eminent to understand the complexity of Malaysian wetlands ecosystem structure, and also develop appropriate management with robust monitoring tools to ensure their ecological sustainability. The study aimed to determine and compared the population and occupancy estimates of selected rail species namely Porphyrio porphyrio indicus and Amaurornis phoenicurus, and other water and terrestrial dependent avian species in Paya Indah and Putrajaya wetlands, Peninsular Malaysia. The study also determined the environmental factors that influenced the occurrence of water birds and terrestrial birds particularly Porphyrio porphyrio indicus (PPI) and Amaurornis phoenicurus (AP), and to develop their habitat suitability models in Paya Indah (PIW) and Putrajaya (PW) wetlands, Malaysia. Distance sampling point count technique using stratified random design was employed to survey avian (from November 2016 to December 2018) from a total of 57 and 54 point stations established around 14 and 24 lakes in PIW and PW respectively. An automatic linear modelling algorithm (ALMA) and geographic information systems were employed to compute the importance ratios of 17 environmental factors (hydrology, climatic, waterscape, and landscape factors). A total of 124,032 and 125,643 bird observations were recorded in PIW and PW from November 2016 to December 2018. The results showed that the terrestrial birds in PIW had higher observed individuals (n = 104,872), species diversity (N = 7.25), richness (R1 = 13.25), evenness (E = 0.92) as compared to the terrestrial birds in PW (n =97340; N = 7.84; R1 = 24.00, E = 0.93). All the observed bird individuals and estimated indices were significantly different except for the Pielou’s J evenness index. However, PW had the highest observed water bird individuals (n=28,303) species diversity (N = 7.60), richness (R1 = 26.73), evenness (E = 0.73) as compared to the water birds in PIW (n =19,160; N = 7.10; R1 = 15.60, E = 0.79). The ALMA results showed that the maximum and minimum weights of the environmental factors are land use/land cover (LULC) and water dissolved oxygen for Porphyrio porphyrio indicus in PIW, while the atmospheric pressure and Normalized Dominant Water Index (NDWI) in PW. This implies that environmental factors significantly contributed to occurrence of the bird species. Also, the maximum and minimum weights of the factors are water turbidity and electrical conductivity for Amaurornis phoenicurus in PIW, while the atmospheric pressure and six water parameters in PW. Large areas of PW were classified more suitable for terrestrial and water birds than PIW due to the favourable atmospheric pressure, LULC, rainfall, wind speed, relative humidity and NDWI. This approach of ranking the important environmental variables criteria using ALMA is very important to conservationist as it presents them with a tool to understand which factor affects the population of birds in their respective habitats. Thus, the models’ adoption as management tools coupled with a robust population monitoring database will enhance the management effectiveness of the species and wetlands. Thus, these wetland habitats need to be conserved in order to increase the population, perpetuity and sustainability of the avian species in the future.